EFFECT OF CORRELATION BETWEEN ROCK PROPERTIES WITH WATER DISCHARGE BY RAINFALL TO LEVEL OF LANDLIDE IN THE CITARUM WATERSHED 20 – 0 KILOMETER, WEST JAVA, INDONESIA - Sudrajat, Muhammad Firzatullah; Abdurrohman, Muhammad Jihad; Alam, Boy Syah (MATTER: International Journal of Science and Technology, 2017)
Citarum River is one of the longest rivers in West Java, Indonesia, with coordinate 7°4’31"S 107°44’53"E. Citarum river has an upstream which located in the region of Neglawangi, Kertasari, and has a downstream in the northern coast of Bekasi. A lot of people domiciled on the watershed of Citarum. Natural disaster such as landslide has become a common thing for people who live around the watershed of Citarum. Study of rock properties located in Citarum River may explain why landslides often occur in areas of Citarum River. The rock sample was conducted at three different stations with each station has a different rock properties. High rainfall causes water flow in the river rises. With the high discharge of water by high rainfall certain rock properties that have a low resistance to water will be easily eroded and causes the soil above the rock properties vulnerable to landslides.